Structural characterization of Ti-15Mo alloy used as biomaterial by Rietveld method - Severino Martins, Jose Roberto [UNESP]; Grandini, Carlos Roberto [UNESP] (American Institute of Physics (AIP), 2012)
The biochemical and mechanical behavior of titanium alloys has been studied extensively for a variety of applications in the aerospace and biomedical fields. In the literature, there are studies that relate the microstructure and the phases of the material with its properties; however, there is little information that quantifies each phase and relates this to its properties. In addition, little has been done to analyze the effects of oxygen and heat treatment on the alloy's structure. In this paper, the effect of doping with oxygen and the effect of heat treatments on structural properties of Ti-15Mo alloy used as biomaterials is examined using scanning electron microscopy, x-ray diffraction, and diffractogram analysis using the Rietveld method. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4707920]